A HISTORICAL STUDY OF EDUCATIONAL AND SOCIAL CONTRIBUTIONS OF CATHOLIC MISSIONARIES IN TIRUNELVELI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The aim of this article is to highlight the educational and social contributions of Catholic Missionaries in Tirunelveli District of Tamil Nadu. Christianity in India is as old as that of Christ himself. St. Thomas one of the Apostles of Christ came to India and spread Christianity in Kerala and Malabar coast. After along interval Portuguese Missionaries came to India and converted a number of people in Tirunelveli district into Christianity . The Cradle of Christianity in the composite Tirunelveli district were Thoothukudi, the whole coastal areas of the gulf of Mannar upto Kanniyakumari, KamaNayakkanpatti, Kayathar and Vadakkankulam. The first Romancatholic Mission that visited Thoothukudi was in the year 1532. But the mass conversion of Paratavars lived in Gulf of Mannar have taken place in 1536.